MTT-Based Evaluation of HepG2 Cell Cytotoxicity Induced by a Polyherbal Extract of Medicinal Plants with Reported Anticancer Properties (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Hepatocellular carcinoma (HCC) is a highly aggressive liver cancer with a poor prognosis, necessitating timely diagnosis and effective treatment strategies. Conventional therapies, including liver transplantation, chemotherapy, targeted drugs, and herbal remedies, provide limited curative outcomes and mainly aim to extend survival and alleviate symptoms. This study investigated the anticancer activity of a polyherbal formulation on HepG2 cell lines. The preparation consisted of hydro-alcoholic and ethanolic extracts of Andrographis paniculata, Annona muricata, Eclipta alba, and Aegle marmelos, all recognized for their anticancer, antioxidant, and hepatoprotective properties. Assessment via cell viability assays revealed a significant reduction in cancer cell survival upon treatment. The observed effects are likely due to synergistic interactions among the extracts, targeting multiple cancer-associated pathways such as apoptosis induction, inhibition of cell proliferation, and reduction of oxidative stress. These findings suggest the potential of polyherbal formulations as complementary therapies for HCC. However, further in vivo and clinical studies are necessary to confirm efficacy, determine safe and effective dosages, and establish comprehensive safety profiles. This work highlights the importance of integrating traditional herbal knowledge with modern research to develop innovative strategies for HCC management.